Physico-Chemical and Bacteriological Study of Anti-Tuberculosis Drug with Alkaline Earth Metals - Shrivatava, Sarita; Kumar Gupta, Pradeep (Asian Journal of Chemistry, 2012)
The avidity of pyraziamide (pyrazie-carboxamide, PZA) for the ions of alkaline earth metals, have been measured and recorded in the form of stability constant and free energy changes, using Bjerrum Calvin pH titration technique as adopted by Irving-Rossoti at 30 ºC ionic strength with KNO3. The order of stability obtained for the alkaline earth metal ion follows the order of e2/r ratio, electronegativities, second ionization potential and sum of the first and second ionization potential of the meal ions.